Application of Brain Based Learning Strategies to Improve Higher Order Thinking Skill and Learning Outcomes of Historical Subjects in Social Sciences Class XI Students in Jenggawah High School, Academic Year 2018/2019 - Nisa Amalia Agustin; Nurul Umamah; Mohamad Na'im (JURNAL HISTORICA, 2020)
Abstract Historical learning develops historical thinking skills which form the basis for students to develop high-level thinking skills. Based on observations of historical learning in class XI IPS 2 Jenggawah Public High School has the ability related to the low level of high-thinking skills, things discussed: (1) the material presented by educators only focuses on the facts of the study in accordance with the findings and figures from history; (2) 80% of students are only able to answer questions in the cognitive domains C1 and C2; (3) learning methods used in the classroom still use conventional learning methods. Based on these considerations, brain-based learning strategies are used to improve high-level thinking skills and student learning outcomes. The purpose of this study was to improve the high-level thinking skills of students in class XI IPS 2 through the application of brain-based learning strategies in learning history in the State High School of Senior High School. The design of the study using the Kemmis and Taggart models, the method of data collection uses the observation, interview, documentation and test models. The results showed the percentage of high-level thinking skills of students, as follows: (1) in the first cycle of analysis indicators of 58.59%, in the second cycle was 73.44%, and in the third cycle 81.30%; (2) on the second cycle indicators obtained at 52.34%, in the second cycle obtained at 68.75%, and in the third cycle 79.70%; (3) on the indicator of creating cycle 1 obtained at 48.44%, in cycle 2 it was 64.06%, and in cycle 3 it was 76.60%. While the learning outcomes of students in cycle 1 obtained an average of 70.5. In cycle 2 it is 77.03 and in cycle 3 is 78.93. Keywords: Brain Based Learning, Higher Order Thinking Skill, Hasil Belajar